Auditoría de Gestión al Área de Crédito de la Cooperativa de Ahorro y Crédito Futuro Lamanense, ubicado en el cantón La Mana período 2018. - Paz Banda, Alexandra Jacqueline (2020)
The main objective of the management audit is to discover deficiencies or irregularities in some of the parts of the company and to indicate the possible solution, helping the management to achieve a more effective administration. Therefore, it was considered essential to carry out a management audit of the credit area in the “Futuro Lamanense” Credit Union, in La Maná canton, period 2018. For this purpose, exploratory research and descriptive research were used facilitating the knowledge of the activities of the management carried out in the cooperative, field research for the development of the interview, surveys of employees and partners and the review of the documentation, additional was complemented with bibliographic research that supported the theoretical basis of the variables in study. Through the preliminary knowledge phase, it was possible to demonstrate that there is non-compliance of the partners in terms of credit payments, in addition there is no specific internal control for the credit area, with this, the threat of increased rates of delinquency and the collection of interest accumulated between the partners increase. Through the application phase of the management audit through internal control with the COSO I approach, a Risk level = 29 % could be determined, and a confidence level = 71%, it was also possible to establish that the highest index late payment was evidenced in the consumer credit with 29.68% for the month of January 2018, however, it was drastically reduced on December same year. And finally, in the final report of the management audit, the results obtained in the development of the management audit were presented, emphasizing the findings with their respective conclusions and recommendations that, when applied, directly will benefit the administrative, partners, employees and customers of the Credit Union “Futuro Lamanense”.